Thermo‐ and CO2‐triggered swelling polymer microgels for reducing water‐cut during CO2 flooding. Issue 4 (26th July 2019) - Tian, Qirui; Han, Peihui; Li, Bo; Feng, Yujun
ABSTRACT: CO2 has been widely used in the process of enhanced oil recovery (EOR) over decades. However, the heterogeneity of oil reservoirs renders CO2 to flow preferentially into highly permeable zones, leaving tight areas unswept with oil unrecovered in these areas. While conventional water‐swelling gels were used for blocking the "channeling" path, most of them experience the risks of shrinkage under high temperature and CO2 ‐induced acidic environment. Here, we developed double swelling smart polymer microgels (SPMs) triggered by both heat and CO2 . Such SPMs were prepared by copolymerization of acrylamide (AAm) in combination with N, N ‐2‐(dimethylamino)ethyl methacrylate (DMAEMA) and [2‐(methacryloyloxy) ethyl]dimethyl‐(3‐sulfopropyl) ammonium hydroxide (SBMA), and with N, N′ ‐methylene bisacrylamide (MBA) as the crosslinker. These SPMs swell when temperature is higher than 65 °C or in the presence of CO2, with an ameliorative salinity tolerance ability. Artificial sand pack flooding carried by SMPs at 65 °C showed an elevated plugging efficiency at around 97% under a simulated pressurization at 5 MPa, proposing a valid candidate for future EOR applications during CO2 flooding. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48305. Abstract :